2000
DOI: 10.1007/s002280050701
|View full text |Cite
|
Sign up to set email alerts
|

Structure-effect relationships of amiodarone analogues on the inhibition of thyroxine deiodination

Abstract: It is likely that the degraded products of AMI could be responsible for thyroid dysfunction toxicosis in AMI therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
15
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 24 publications
2
15
0
Order By: Relevance
“…This compound was prepared with a yield of 60% as described previously (Ha et al, 2000). Melting point (146.4 -146.9°C) and NMR data (not shown) were in agreement with the previous report.…”
Section: Chemistry and General Methodssupporting
confidence: 87%
See 1 more Smart Citation
“…This compound was prepared with a yield of 60% as described previously (Ha et al, 2000). Melting point (146.4 -146.9°C) and NMR data (not shown) were in agreement with the previous report.…”
Section: Chemistry and General Methodssupporting
confidence: 87%
“…All the amiodarone metabolites or derivatives used were synthesized from B2. B2 was synthesized as described previously (Ha et al, 2000). The derivatives B2-O-Et-NH-ethyl, B2-O-Et-NH 2 , B2-O-Et-N-dimethyl, and B2-OEt-N-dipropyl were prepared by condensing B2 with the respective 2-chloroethyl amine hydrochloride salts in the presence of K 2 CO 3 .…”
Section: Synthesis Of B2-o-et-nh-ethylmentioning
confidence: 99%
“…A Friedel–Crafts acylation next introduces the aryl ring at the 3-position. Demethylation, iodination and a final alkylation with a diethylaminoethane fragment yields amiodarone [115117]. …”
Section: Reviewmentioning
confidence: 99%
“…This concept remains, however, largely to be established as several alternative mechanisms have been proposed to explain the hypothyroid-like action of the agents mentioned above. It has been showed that 10 may inhibit peripheral conversion of 2 to 1 through interaction with deiodinases [69,70], inhibit cellular uptake of 2 and/or 1 [71] or act directly on the on the cardiac contractility.…”
Section: Debated Mechanism Of Action: Amiodarone and Its Structural Amentioning
confidence: 99%